Targeting of Secretory Proteins as a Therapeutic Strategy for Treatment of Nonalcoholic Steatohepatitis (NASH) - Kim, Kyeongjin (Int J Mol Sci, 2020)
Nonalcoholic steatohepatitis (NASH) is defined as a progressive form of nonalcoholic fatty liver disease (NAFLD) and is a common chronic liver disease that causes significant worldwide morbidity and mortality, and has no approved pharmacotherapy. Nevertheless, growing understanding of the molecular mechanisms underlying the development and progression of NASH has suggested multiple potential therapeutic targets and strategies to treat this disease. Here, we review this progress, with emphasis on the functional role of secretory proteins in the development and progression of NASH, in addition to the change of expression of various secretory proteins in mouse NASH models and human NASH subjects. We also highlight secretory protein-based therapeutic approaches that influence obesity-associated insulin resistance, liver steatosis, inflammation, and fibrosis, as well as the gut–liver and adipose–liver axes in the treatment of NASH.